Sickness Presenteeism among the Self-employed and Employed in Northwestern Europe-The Importance of Time Demands - Mikael Nordenmark; Emma Hagqvist; Stig Vinberg (Elsevier, 2019)
Background: European policymakers encourage individuals to become self-employed because it is a way to promote innovation and job creation. It can be assumed that health and well-being among the self-employed and managers in small-scale enterprises are particularly crucial in this enterprise group because the smallness of the enterprise makes its members vulnerable. Earlier studies have indicated that the self-employed have a high working pace and work for long and irregular hours, indicating that it can be difficult to stay at home because of sickness. The purpose of this study is to investigate the occurrence of sickness presenteeism among the self-employed in relation to the organizationally employed and to analyze whether any differences can be explained by higher work demands among the self-employed. Methods: The study is based on the fifth European survey on working conditions (2010) and includes the northwestern European countries in the survey. The questions cover a wide range of topics designed to meet the European Union's political needs. The main variables in this study are sickness presenteeism and several indicators of time demands. Results: The results show that the self-employed report a higher level of sickness presenteeism than the employed: 52.4 versus 43.6%. All indicators of time demands are significantly related to the risk for sickness presenteeism, also when controlling for background characteristics. Conclusion: The results confirm that the level of sickness presenteeism is higher among the self-employed and that high time demands are a major explanation to this. Keywords: Northwestern Europe, Organizationally employed, Self-employed, Sickness presenteeism, Time demands